Artificial Intelligence in Transportation: A Review - Miss. Asawari Satish Isalkar; Dr. Rajeshkumar U. Sambhe (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The growing use of Artificial Intelligence, along with its factors is rapidly increasing in various fields now a days. It providing the opportunity to upgrade the efficiency of various industries and business, including transportation sector. AI gives more efficient service to Public Transportation to enhance the urban mobility. The goal of AI to acquire the knowledge about reasoning, planning, perception and deal with objects. The AI for transportation is assist to reduce the risk and enhance the safety. AI applications is help to solve the challenges such as travel demand, CO2 emissions, safety concerns, and fuel waste. The challenges and desideratum faces during transportation can be easily addressed by AI algorithm. This paper stretches a view about the AI technique use in worldwide Transportation of methodology, applications, future of AI in deep learning and limitations.